Innovating Community-Based Change in the Area of Weight Loss and Lifestyle Change: The Power of Ethical Relationships and Leadership - Liu, James; Valdes, Evan; Sarich, Jenn; Finau, Gloria; Nua, Alosina (Jurnal Psikologi Sosial, 2024)
Obesity is increasing around the world, with lower income individuals showing more obesity than wealthier ones in high income countries. Addressing this issue, Te Whatu Ora (Ministry of Health) and Total Healthcare (THC, a large Primary Health Organisation) worked together to put together a “unique and unsolicited proposal” (instead of competitive tender) to fund Brown Buttabean Motivation (BBM) to provide its 12 week From the Couch (FTC) lifestyle change and weight loss program more widely to a predominantly Māori and Pacific clientele in South Auckland. Results from a formative evaluation of 109 individuals struggling with obesity (BMI>=30) across 3 cohorts showed weight loss of 7.1 kg from an initial average weight of 173.1 kg, and mental health gains (i.e. only 20% showing depressive symptoms at the end compared to 60% at the start) for the 57% who completed the program. THC nurses, doctors, and health coaches contributed to and supported delivery of FTC, which followed BBM’s well-defined program of motivating lifestyle change. It was found that a supportive environment (no judgement) and peer-based education (accepting no excuses) motivated clients through not only diet and exercise training, but also through social media where Facebook groups formed helpful communities that supported face-to-face work in the gym. We close with discussion of BBM’s principles for success, and how extensible this might be to other communities.